Wartime workers gathered in a YWCA parlor in New York City in 1918. - Unknown:::Creator::::::::::::
"Wartime workers gathered in a YWCA parlor in New York City in 1918." From: Smith, p. 36. Group of 18 women, most in uniforms, gathered in a small room. Many are holding tea cups and saucers.